Rational synthesis of normal, abnormal and anionic NHC–gallium alkyl complexes: structural, stability and isomerization insights12. Issue 10 (14th October 2015) - Uzelac, Marina; Hernán-Gómez, Alberto; Armstrong, David R.; Kennedy, Alan R.; Hevia, Eva
<x xml:space="preserve">Abstract</x> Using two alternative methodologies, new light has been shed on the stability and rational formation of abnormal NHC–gallium complexes.